Study of the effect of micelle-forming surfactants on the strength of cellular reactive powder concrete - Shishkina, Alexsandera (Eastern-European Journal of Enterprise Technologies, 2016)
Changes in the cement hydration rate affect the concrete compressive strength formation rate. Under certain conditions, an increase in the cement hydration rate improves the concrete strength under compression. This is especially true of foam concrete. The paper examines the effect of micellar solutions, which are a mixture of the micelle-forming surfactant and conventional molecular surfactant. A feature of the research is the study of the effect of micelle-forming surfactants on the strength of foam concrete, which is commonly manufactured using molecular surfactants. The research revealed that these micellar solutions change the pattern of foam concrete strength formation, namely, increase the strength formation rate, in particular, of reactive powder foam concrete, especially in the initial period, and maintain their high compressive strength at later stages of hardening. It is proved that the micellar catalysis can be used to manage the processes of cement hardening and strength formation of cement stone, produced in the cement hydration, thereby reducing the time to achieve the design foam concrete strength, or enhancing the absolute compressive strength of such concrete at 28 days.